2014
DOI: 10.1111/cxo.12169
|View full text |Cite
|
Sign up to set email alerts
|

Screening for keratoconus suspects among candidates for refractive surgery

Abstract: This review examines methods for estimating the risk of post‐surgical ectasia in candidates for refractive surgery by establishing a diagnosis of keratoconus suspect as a contraindication for proceeding with surgery. Notwithstanding the desirability of achieving 100 per cent sensitivity, any associated reduction in specificity and increased numbers of false positives might deny some candidates the opportunity to proceed with refractive surgery. The introduction of a model for the risk of ectasia involving both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…TGFBI is a cytokine that interacts with the extracellular matrix proteins and plays a role in tissue injury and repair. 27 Sporadic KC cases, by definition, do not have a genetic basis or influence on their disease development. 10 A genetic diagnostic tool is desirable.…”
Section: Genetic Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…TGFBI is a cytokine that interacts with the extracellular matrix proteins and plays a role in tissue injury and repair. 27 Sporadic KC cases, by definition, do not have a genetic basis or influence on their disease development. 10 A genetic diagnostic tool is desirable.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…10 A genetic diagnostic tool is desirable. 27 Ideally, family members who do not have or are not at risk for developing KC and who can be used as controls in studies of familial KC could be identified with confidence. 27 Sporadic KC cases, by definition, do not have a genetic basis or influence on their disease development.…”
Section: Genetic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…This complication is of serious concern because patients undergo LASIK surgery with practically healthy eyes and have other options for vision correction. The methods used to estimate the risk of post-surgical ectasia have been well documented in the literature [2][3][4]. Despite good ability to predict this complication, current studies continue to report cases of iatrogenic keratectasia [5,6].…”
Section: Introductionmentioning
confidence: 99%